Kecemasan pada anggota polri di polda DIY: bagaimana peran stresor lingkungan kerja? - Muhammad Bahrori Rohza; FX Wahyu Widiantoro (SUKMA : Jurnal Penelitian Psikologi, 2026)
The policing profession is inherently exposed to high-risk demands and organizational dynamics that potentially disrupt the mental well-being of personnel. This study was conducted to examine the phenomenon of mental health issues within law enforcement with the aim of testing the effect of work environment stressors on anxiety levels among Indonesian National Police members. Employing a non-experimental quantitative approach with correlational, data were collected through digital surveys using instruments constructed based on the job stressor theory by French & Caplan (1972) and the anxiety indicators defined by Hendra (2024). A total of 150 active members at the Special Region of Yogyakarta Regional Police were selected as participants using a simple random sampling technique. The collected numerical data were then analyzed using simple linear regression statistical tests after fulfilling the prerequisite normality and linearity tests. The descriptive analysis results indicate that the respondents' work stressor levels are in the low category since the workload is considered proportional to personal capacity. Meanwhile, the inferential analysis results prove a positive and significant effect of work environment stressors on anxiety, with an effective contribution of 21 percent. This implies that the police institution must implement proactive policies, such as integrating comprehensive psychological counseling programs and stress management training, to maintain emotional stability and optimize personnel performance in the field.   Profesi kepolisian secara inheren dihadapkan pada tuntutan tugas bersiko tinggi dan dinamika organisasi yang berpotensi mengganggu kesejahteraan mental personel. Penelitian ini dilakukan untuk mengkaji fenomena gangguan kesehatan mental di lingkungan penegak hukum dengan tujuan menguji pengaruh stresor lingkungan kerja terhadap tingkat kecemasan pada anggota Kepolisian Republik Indonesia. Menggunakan pendekatan kuantitatif korelasional, data dikumpulkan melalui survei digital dengan instrumen yang dikonstruksi berdasarkan teori stresor kerja French & Caplan (1972) dan indikator kecemasan Hendra (2024). Sebanyak 150 anggota aktif di Kepolisian Daerah Istimewa Yogyakarta dipilih sebagai partisipan menggunakan teknik penarikan sampel acak sederhana. Data numerik yang dihimpun kemudian dianalisis menggunakan uji statistik regresi linear sederhana setelah memenuhi uji prasyarat normalitas dan linearitas. Hasil analisis deskriptif menunjukkan bahwa tingkat stresor kerja responden berada dalam kategori rendah karena beban tugas dinilai masih sesuai dengan kapasitas personal. Sementara itu, hasil analisis inferensial membuktikan adanya pengaruh positif dan signifikan dari stresor lingkungan kerja terhadap kecemasan, dengan kontribusi efektif sebesar 21 persen. Implikasinya, institusi Polri perlu merumuskan kebijakan yang lebih proaktif, seperti penguatan program konseling psikologis yang terintegrasi dan pelatihan manajemen stres, guna menjaga stabilitas emosional serta mengoptimalkan kinerja anggota di lapangan.